IMPLEMENTATION OF THE POLICY ON THE IMPLEMENTATION OF THE VILLAGE FINANCIAL SYSTEM APPLICATION (SISKEUDES) IN THE MANAGEMENT OF VILLAGE ALLOCATION FUNDS IN SUMORAME VILLAGE - Labibi, Silda; Sukmana, Hendra (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to evaluate the implementation of the Village Financial System (Siskeudes) application policy in managing the Village Allocation Fund (DAD) in Sumorame Village, Candi Sub-district, Sidoarjo Regency. Method: A descriptive qualitative approach was employed, analyzed using the DeLone and McLean Information System Success Model (2003), which encompasses six key dimensions: system quality, information quality, service quality, system use, user satisfaction, and impact on individuals and organizations. Results: The findings indicate that the Siskeudes application has been effectively implemented, contributing significantly to improved transparency, accountability, and efficiency in village financial management. The system is actively utilized by village officials for daily operations and has proven capable of automatically generating various financial reports. However, challenges persist, particularly limited human resources and internet infrastructure, although these are mitigated by technical support from the district government and continuous system updates. Novelty: This study provides a comprehensive assessment of Siskeudes implementation at the village level by applying the DeLone and McLean model, highlighting the system’s role in promoting digital transformation in financial governance and emphasizing the critical need to strengthen human resource capacity and infrastructure for sustainable digitalization.